The curious case of chemotaxis in soft rot Pectobacteriaceae - Nasaruddin, Afnan Shazwan, author; Charkowski, Amy O., advisor; Leach, Jan E., committee member; Trivedi, Pankaj, committee member; Heuberger, Adam L., committee member (Colorado State University. Libraries, 2021)
Soft rot Pectobacteriaceae, Dickeya and Pectobacterium, are notorious for causing blackleg and soft rot diseases on more than 50% angiosperms such as potato, tomato, carrot, cabbage, and rice. In the United States, soft rot Pectobacteriaceae causes at least $40 million losses of potato each year. Flagellar motility is important for soft rot Pectobacteriaceae virulence. Chemotaxis, which controls flagellar motility towards a conducive environment or away from hostile conditions, is essential for initial stages of infection. Chemotaxis is mediated by chemoreceptors known as methyl-accepting chemotaxis proteins. Genomic analyses of soft rot Pectobacteriaceae and closely related animal pathogens and non-pathogenic bacteria in order Enterobacteriales showed that soft rot Pectobacteriaceae genomes are enriched in methyl-accepting chemotaxis proteins. Furthermore, soft rot Pectobacteriaceae methyl-accepting chemotaxis proteins contain more diverse ligand binding domains compared to other species in Enterobacteriales. This study suggests the importance of chemotaxis for soft rot Pectobacteriaceae pathogenicity and opens up possibilities for future research in targeting chemotaxis for plant disease management. In E. coli, the alternative sigma factor FliA is required for transcription initiation in motility and chemotaxis genes. To determine how chemotaxis is regulated in Dickeya, we conducted an RNA-sequencing experiment using a wild-type strain and a fliA mutant of D. dadantii 3937 grown in minimal media with glycerol or glucose. We found that the FliA sigma factor did not regulate methyl-accepting chemotaxis genes in Dickeya, several virulence genes were upregulated in glucose, and some genes postulated to be regulated by PecS were upregulated in glycerol. It is still a mystery as to which sigma factor regulates the chemotaxis genes in Dickeya, however, my work demonstrates that the regulation of chemotaxis in plant pathogens differs from closely related animal pathogens in the same order.
Keywords: Pectobacteriaceae; soft rot disease; potato; chemotaxis